A cluster randomised crossover trial of single resilience and professionalism tutorials among undergraduate medical students - David Byrne; Anne Hickey; Denis Harkin; Aine Ryan; Catherine Moran; Fiona Boland; Jan Illing; Lorna Staines; Mohamed Abdelnasser; Lisa Mellon; Caroline Kelleher; Frank Doyle (Medical Education Online, 2025)
Background Evidence suggests that targeted interventions can improve medical students’ perceptions of professionalism and professional identity formation, resilience and coping skills. However, it is unclear how many educational sessions are required for a meaningful impact. We aimed to determine the impact of single resilience/professionalism tutorials on Year 1 medical students’ coping self-efficacy and resilience and perceptions of professionalism and professional identity formation. We also conducted a qualitative process evaluation.Methods A cluster crossover design was used to evaluate tutorials. Student groups were randomly allocated to ‘resilience first’ and ‘professionalism first’ classes, followed immediately by the alternative tutorial. Students (n = 106) completed the Coping Self-Efficacy Scale (CSES) and Penn State Questionnaire on Professionalism (PSCOM) before the first tutorial, between tutorials, and after the second tutorial. Differences in CSES and PSCOM scores between groups were assessed using multivariate analysis of variance. Findings were presented to students (n=6) and focus group data were analysed using reflective thematic analysis.Results Within-group effects showed significant increases in scores for CSES and PSCOM, but irrespective of original group allocation. Qualitative results suggested three themes: positive aspects, limitations, and improving training. Several logistical issues were identified that may have inhibited tutorial efficacy.Conclusion While we found increased self-efficacy and professionalism scores, these could not be related to the efficacy of respective single tutorials, suggesting that multiple tutorials are required to impact these outcomes. While cross-over designs are feasible to implement, logistical issues may detract from their efficacy. Tutorials could potentially be improved by introducing more interactive learning methods.